Colombia: Territory for investment in non-conventional renewable energy to electric generation - Ñustes-Cuellar, Wiston Andrés; Rivera-Rodriguez, Sergio Raúl (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
This document corresponds to a reflection paper showing different research results on the picture of the current electricity sector in Colombia and how it has led to contemplate the inclusion of Non-Conventional Renewable Energy (FNCER) in a short and medium term. First, a discussion of the evolution of the electricity industry in Colombia at recent decades is presented, and the current problems and vision of the different agents of the electricity sector are developed. Finally, financing sources (nationally and internationally) needed to carry out projects of Non-Conventional Sources of Distributed Generation and Renewable Energy is presented.